Comparison of Hedging Strategies between Vietnam and the Philippines amid the U.S.-China Strategic Competition - Liu, Qianqian (International Journal of Social Sciences and Public Administration, 2024)
This paper examines and compares the hedging strategies of Vietnam and the Philippines towards both the United States and China. The study is grounded in the context of heightened geopolitical and economic rivalry, where smaller states confront the challenge of navigating the complex dynamics between these two major powers. Hedging, as a strategy to manage uncertainties and risks, is analyzed through a comparative case study approach, focusing on five key components: indirect balancing, dominance denial, economic pragmatism, binding engagement, and limited bandwagoning. The findings indicate that both Vietnam and the Philippines utilize hedging, but with differences. Vietnam's approach is more systematic and comprehensive, involving all five components, whereas the Philippines' strategy is more reactive and less planned, with a stronger tilt towards the U.S. due to shared democratic values and historical ties. The research underscores the nuanced nature of hedging and its implications for middle powers navigating great power rivalries in the Indo-Pacific region.